The structural oppression of women by markets: the continuum of sexual violence and the online pornography market. Issue 1 (2nd January 2021) - McVey, Laura; Gurrieri, Lauren; Tyler, Meagan
ABSTRACT: This paper assembles emerging scholarship attendant to the marginalisation of people by market structures of power and dominance. We conceptualise this as market violence and locate one group of people largely missing from this conversation: women. To theorise women's structural subordination in the marketplace we introduce several key tenets of radical feminist theory. Then, applying the continuum of sexual violence, we conceive markets as structures of sexual violence. Through the online pornography market, we find the market system (in producing and distributing women as commodities) is perpetrating a complex range of (often difficult to define) forms of sexual violence. We then reveal the market's pervasiveness as a form of sexual harassment. To finish, we offer the continuum as a broader conceptualisation for future market violence scholarship.